2013
DOI: 10.1017/s1092852913000606
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life before and after cosmetic surgery

Abstract: This article reviews the literature regarding the impact of cosmetic surgery on health-related quality of life (QOL). Studies were identified through PubMed/Medline and PsycINFO searches from January 1960 to December 2011. Twenty-eight studies were included in this review, according to specific selection criteria. The procedures and tools employed in cosmetic surgery research studies were remarkably diverse, thus yielding difficulties with data analysis. However, data indicate that individuals undergoing cosme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In addition, the timeline of the follow-up is a relevant aspect in the analysis of the PROMs. The positive change in bodily and mental perception and the quality of life is especially obvious in the first 12 months after surgery [149]. A meta-analysis performed by Yang et al in 2018 verified this in a review of all rhino-specific PROMs and confirmed the improved quality of life, in particular in the first 12 months and in young patients [150].…”
Section: Quality Of the Subjective Patient Perception Of Prom In Rhinmentioning
confidence: 90%
“…In addition, the timeline of the follow-up is a relevant aspect in the analysis of the PROMs. The positive change in bodily and mental perception and the quality of life is especially obvious in the first 12 months after surgery [149]. A meta-analysis performed by Yang et al in 2018 verified this in a review of all rhino-specific PROMs and confirmed the improved quality of life, in particular in the first 12 months and in young patients [150].…”
Section: Quality Of the Subjective Patient Perception Of Prom In Rhinmentioning
confidence: 90%
“…A comparative study of Bensoussan et al evaluated studies that had assessed quality of life in rhinoplasty to compare their results and extract conclusions about the effectiveness and accuracy of methods being used. They concluded that measuring quality of life in facial cosmetic surgery is a complex and difficult process.…”
Section: Discussionmentioning
confidence: 99%
“…The rhinoplasty group showed significant reduction in psychological distress postoperatively, especially in the fields of negative self-concept and selfconsciousness, indicating that rhinoplasty improves quality of life in these patients. A comparative study of Bensoussan et al 25 evaluated studies that had assessed quality of life in rhinoplasty to compare their results and extract conclusions about the effectiveness and accuracy of methods being used. They concluded that measuring quality of life in facial cosmetic surgery is a complex and difficult process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an improvement in life quality increases until about 1 year postsurgery. Conversely, such changes are not so evident later on [31]. …”
Section: Introductionmentioning
confidence: 99%